Multiple intra-articular injections of allogeneic bone marrow-derived stem cells potentially improve knee lesions resulting from surgically induced osteoarthritis: an animal study. (July 2019) - Mahmoud, E. E.; Adachi, N.; Mawas, A. S.; Deie, M.; Ochi, M.
Abstract : Aim: Mesenchymal stem cells (MSCs) have several properties that may support their use as an early treatment option for osteoarthritis (OA). This study investigated the role of multiple injections of allogeneic bone marrow-derived stem cells (BMSCs) to alleviate the progression of osteoarthritic changes in the various structures of the mature rabbit knee in an anterior cruciate ligament (ACL)-deficient OA model. Materials and Methods: Two months after bilateral section of the ACL of Japanese white rabbits aged nine months or more, either phosphate buffered saline (PBS) or 1 x 10 6 MSCs were injected into the knee joint in single or three consecutive doses. After two months, the articular cartilage and meniscus were assessed macroscopically, histologically, and immunohistochemically using collagen I and II. Results: Within the PBS injection (control group), typical progressive degenerative changes were revealed in the various knee structures. In the single MSC injection (single group), osteoarthritic changes were attenuated, but still appeared, especially in the medial compartments involving fibrillation of the articular cartilage, osteophyte formation in the medial plateau, and longitudinal tear of the meniscus. In the multiple-injections group, the smoothness and texture of the articular cartilage and meniscus were improved. Histologically, absence or reduction in matrix staining and cellularity were noticeable in the control and single-injection groups, respectively, in contrast to the multiple-injections group, which showed good intensity of matrix staining and chondrocyte distribution in the various cartilage zones. Osteoarthritis Research Society International (OARSI) scoring showed significantly better results in the multiple-injections group than in the other groups. Immunohistochemically, collagen I existed superficially in the medial femoral condyle in the single group, while collagen II was more evident in the multiple-injections group than the single-injection group. Conclusion: A single injection of MSCs was not enough to restore the condition of osteoarthritic joints. This is in contrast to multiple injections of MSCs, which had the ability to replace lost cells, as well as reducing inflammation. Cite this article: Bone Joint J 2019;101-B:824–831.